ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN RUMAH SUBSIDI DI DESA KEKERI LOMBOK BARAT - Siswanto, Topan (Sekolah Tinggi Ilmu Ekonomi AMM Mataram, 2018)
This study will analyze the influence of cultural factors, personal factors, social factors and psychological factors that will affect the purchase decision of government housing program that is subsidized housing. Where in this study will analyze the subsidized housing located in Kekeri district named housing Graha Kekeri. In this study using the respondent based on the number of units of housing built in Graha Kekeri which amounted to 36 units. This means that there are 36 heads of households who were respondents. From the research result, only the cultural factor and personal factors have significant influence on the purchase of social subsidy graha housing and kekeri factor while the social factor variable and the psychological factor have no influence to the buying decision of Graha Kekeri. In addition, based on the analysis of determination of independent variables affect the dependent variable by 68%.